(untitled) (Acta Polytechnica CTU Proceedings, 2017)
In this article, we propose a software solution to study HMI of electric and hybrid electric vehicles in vehicle simulators. We will start with the description of a development process of a physical model for HEV simulation in IGNITE software and equation-based language Modelica. A short introduction to the language, its possibilities, and explanation, why it is more suitable for the development of such models (vehicle powertrain), are presented in the first part of the article. A fusion mechanism of the physical engine with the model by means of FMU (Functional Mock-up Interface) is also described in this part The second part is dedicated to the description of the model constructed in third party software IGNITE. This model has a detailed calculation of energy consumption and energy flow based on the selected control strategy. The last part of the article describes a possible experiment methodology.